How Often Do Verbs Co-Occur with Relevant Events? Examining Parent and Toddler Speech in Latin America and the Us - Fernandez-Tapia, A (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
A basic cognitive ability is the ability to detect patterns in the environment. A key pattern that could be useful in verb learning concerns correspondences between verbs and events. No prior study of verb + event links has included older toddlers or children learning a language other than English. We observed mother-child dyads across two languages/cultures, to ask: how often do young children hear verbs while seeing relevant events in everyday life? In Study 1, monolingual Spanish-speaking dyads (n = 12, 19-36 months old) in Santiago, Chile and Guatemala City, Guatemala were videotaped in their homes in two 45-60-min sessions. Samples were transcribed by fluent Spanish speakers and coded for verbs with referents that could be seen (e.g., forms of "pintar"/"to paint"). For these action verbs, coders then identified whether a relevant event was present; proportions computed to adjust for different amounts of talk. Children produced verbs with events 30% of the time (ave. prop. verb = .30, SE = .09); parents rate was 20% (ave. prop. verb = .20, SE = .05) for a combined rate of 50%. In Study 2, the same procedure was repeated with an English-speaking sample in Austin, Texas (n = 12, 23-36 months old), and similar rates of verb-event co-occurrences in the children s and parents speech were found. Specific verbs spoken by children and parents are reported. In sum, across two languages/cultures, action verbs co-occurred with referents approximately 50% of the time, and many co-occurrences fit the child s actions. These findings are important to inform new empirical studies and guide current verb theories.